The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12035-018-1403-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and Its Role in Diverse Brain Diseases

Abstract: Ferroptosis is a recently identified, iron-regulated, non-apoptotic form of cell death. It is characterized by cellular accumulation of lipid reactive oxygen species that ultimately leads to oxidative stress and cell death. Although first identified in cancer cells, ferroptosis has been shown to have significant implications in several neurologic diseases, such as ischemic and hemorrhagic stroke, Alzheimer's disease, and Parkinson's disease. This review summarizes current research on ferroptosis, its underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
241
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(262 citation statements)
references
References 164 publications
(233 reference statements)
1
241
0
2
Order By: Relevance
“…These lectures and texts generally focused on aggregation and fibrillization alone. However, the current literature is becoming increasingly clear concerning the very important connections between iron and AD, PD, Prion disease, motor neurone disease, and other chronic slowly-progressing neurodegenerative diseases (Biasiotto et al, 2015;Ndayisaba et al, 2019;Weiland et al, 2019). This review emphasizes the complexity of the cellular problem at hand with respect to interactions of iron with certain proteins and small molecules as caused by HF.…”
Section: Resultsmentioning
confidence: 99%
“…These lectures and texts generally focused on aggregation and fibrillization alone. However, the current literature is becoming increasingly clear concerning the very important connections between iron and AD, PD, Prion disease, motor neurone disease, and other chronic slowly-progressing neurodegenerative diseases (Biasiotto et al, 2015;Ndayisaba et al, 2019;Weiland et al, 2019). This review emphasizes the complexity of the cellular problem at hand with respect to interactions of iron with certain proteins and small molecules as caused by HF.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis is implicated in numerous human diseases and pathologies. It has been suggested that ferroptosis plays a role in the progression of degenerative diseases of the kidney, heart, liver, and brain (Feng and Stockwell, 2018); stroke, Alzheimer disease, Huntington disease (HD), and Parkinson disease are among the candidates for neurodegenerative diseases that may involve ferroptosis (Weiland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the ferroptosis pathways has been connected with the growing number of disorders including AD and PD. [ 166 ] Inhibiting ferroptosis by small molecules or by gene knockdown can protect neurons, and improve the cognitive function in the diseased animal. For example, mitochondrial dysfunction and ferroptosis can be suppressed by targeting nuclear factor erythroid 2‐related factor (2NRF2) in neurodegenerative diseases.…”
Section: Safety Challenges Of Nanomedicinementioning
confidence: 99%
“…[ 170 ] For several other ferroptosis inhibitors please refer to the recent review article by Wang and co‐workers. [ 166 ]…”
Section: Safety Challenges Of Nanomedicinementioning
confidence: 99%